The Capability of Developing Arts and Culture Learning in Increasing the Creativity Understanding of Bamban Village Primary School Children - Riska, Rahimatu; Fadila, Khairatul (International Journal of Students Education, 2024)
Art as a field that is based on beauty has a significant role in future arts education. The conceptof art education in elementary school is basically directed at forming attitudes, so that there is a balance of children’s intellectual, intelligence, mental, physical and moral qualities, because at elementary school age, children’s mental and physical development is at a high stage of development so as to optimize their creativity then art education is one of the right methods to use. Therefore, arts educationshould be a forum or means for children to develop and express their creativity. The creativity of children at elementary school age still varies greatly according to their level of maturity and brain development. To improve the development of children’s creativity so that they grow optimally, arts education plays a very important role, namely as a means of facilitating children in expressing their thoughts and souls. Arts and Culture learning has an important role in developing creativity and cultural appreciation in students. This journal discusses the importance of arts and culture education in the context of modern education. We explore effective strategies and approaches in integrating arts and culture into the curriculum, as well as their impact on student development. In this journal, we also examine several challenges faced by arts and culture education and provide recommendations for overcoming these problems. Through a deep understanding of the importance of arts and cultureeducation, it is hoped that we can create a learning environment that enriches and motivates students.